Transforming Heritage Practice in the 21st Century Contributions from Community Archaeology - Jameson, John H.; Musteaţă, Sergiu; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Recent years have witnessed a rapid increase in the fields of cultural heritage studies and community archaeology worldwide with expanding discussions about the mechanisms and consequences of community participation. This trend has brought to the forefront debates about who owns the past, who has knowledge, and how heritage values can be shared more effectively with communities who then ascribe meaning and value to heritage materials. Globalization forces have created a need for contextualizing knowledge to address complex issues and collaboration across and beyond academic disciplines, using more integrated methodologies that include the participation of non-academics and increased stakeholder involvement. Successful programs provide power sharing mechanisms and motivation that effect more active involvement by lay persons in archaeological fieldwork as well as interpretation and information dissemination processes. With the contents of this volume, we envision community archaeology to go beyond descriptions of outreach and public engagement to more critical and reflexive actions and thinking. The volume is presented in the context of the evolution of cultural heritage studies from the 20th century "expert approach" to the 21st century "people-centered approach," with public participation and community involvement at all phases of the decision-making process. The volume contains contributions of 28 chapters and 59 authors, covering an extensive geographical range, including Africa, South America, Central America, Western Europe, Eastern Europe, North America, and Australasia. Chapters provide exemplary cases in a growing lexicon of public archaeology where power is shared within frameworks of voluntary activism in a wide diversity of cooperative settings and stakeholder interactions.
PART 1. Public Archaeology at the Intersections of Heritage and Community -- 1. Creating Opportunities and Managing Expectations: Evaluating Community Archaeology in Ireland -- 2. A tale of the unexpected: a heritage encounter with a new target audience and the sociocultural effects experienced by this community of participants -- 3. Community archaeology in Eastern Europe, An example from the Republic of Moldova -- 4. Heritage and Public Archaeology in South-western Nigeria -- 5. Barriers to community archaeology: reviewing the legal heritage frameworks within the South African context -- 6. Community archaeology can be 'a piece of cake': Key ingredients for community-based approaches -- 7. Ancient Maya House and Forest Garden: Shared Connections -- 8. Heritages in Conflict: Interpreting Controversial History with Community Engagement -- 9. Increasing Heritage Awareness through Community Participation: African-Brazilian community participation in a diversity context -- PART 2. Catalysts for Inclusive Heritage at Cultural Landscapes and Parks -- 10. Shipwrecks and Sport Divers: Florida's Programs in Participatory Preservation Underwater -- 11. Time Traveling in Delaware State Parks: Some Strategies for a Public Participatory Program -- 12. From Performance to Participation: Fostering a sense of shared heritage through archaeology at the Presidio of San Francisco -- 13. Popular Memories and Imagined Futures at the President's House Site: A case study juxtaposing public policy and 'the public' in the determination of archaeological site significance -- 14. Archaeological Commitment to Participation from the Local to the International: Discovering the El Pilar Community -- 15. The Value of Biodiversity Conservation in the Process of Making a Historic Park -- 16. Folklore as landscape biography in the interpretation of cultural landscapes: Great Zimbabwe and North York Moors National Park (England) -- 17. Promoting Descendant Communities in Urban Community Archaeology: A study of Canberra, Australia -- 18. Working with communities and World Heritage places: Local, professional and educational communities and the Port Arthur Historic Site Management Authority -- 19. Reclaiming Rock Art: Descendant Community Investment in Australian and New Zealand Patrimony -- 20. From Forgotten to National Monument: Community Archaeology at a World War II internment camp in Hawai'i -- PART 3. Catalysts for Inclusive Heritage with New Knowledge Creation and Innovation -- 21. Bring it on! Increasing heritage participation through engagement opportunities at unconventional places -- 22. Citizen scientists and open source data: developing a platform for archaeological material in Finland -- 23. Community Archaeology and Engagement at Trellech, Wales -- 24. Documenting and Memorializing Built Heritage through Urban Exploration in Detroit, Michigan -- 25. Like Ripples across a Pond: Catalyzing Heritage Programs through Radical Openness -- 26. Activism from the Archives: changing narratives to engagenew communities -- 27. Reaching out: The participatory culture model and current approaches to the creation new archaeological knowledge with local communities -- 28. Computational Mathematics, Convergence Culture, and the Creation of Archaeological Knowledge and Understanding .
Keywords: Archaeology; Cultural property; Archaeology; Cultural Heritage